2003
DOI: 10.1073/pnas.252785099
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila DEG/ENaC pickpocket genes are expressed in the tracheal system, where they may be involved in liquid clearance

Abstract: The Drosophila tracheal system and mammalian airways are branching networks of tubular epithelia that deliver oxygen to the organism. In mammals, the epithelial Na ؉ channel (ENaC) helps clear liquid from airways at the time of birth and removes liquid from the airspaces in adults. We tested the hypothesis that related Drosophila degenerin (DEG)͞ENaC family members might play a similar role in the fly. Among 16 Drosophila DEG͞ENaC genes, called pickpocket (PPK) genes, we found 9 expressed in the tracheal syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
95
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(99 citation statements)
references
References 43 publications
1
95
0
1
Order By: Relevance
“…The D. melanogaster respiratory system is the trachea, which consists of approximately 10,000 interconnected and branching tubules. Significantly, there are many conserved genes and regulatory components between trachea development in the fly and lung development in mammals (Liu et al, 2003;Horowitz and Simons, 2008). Airway epithelial cells form the trachea, and they are the first line of defense against airborne pathogens.…”
Section: Inflammation/infectious Diseasementioning
confidence: 99%
“…The D. melanogaster respiratory system is the trachea, which consists of approximately 10,000 interconnected and branching tubules. Significantly, there are many conserved genes and regulatory components between trachea development in the fly and lung development in mammals (Liu et al, 2003;Horowitz and Simons, 2008). Airway epithelial cells form the trachea, and they are the first line of defense against airborne pathogens.…”
Section: Inflammation/infectious Diseasementioning
confidence: 99%
“…Liu et al, 2003aLiu et al, ,b, 2012Lu et al, 2012;Starostina et al, 2012;Thistle et al, 2012;Toda et al, 2012;Zelle et al, 2013;Guo et al, 2014;Mast et al, 2014;Vijayan et al, 2014 Larval terminal organ…”
Section: Olfactory and Gustatory Chemoreceptors In Flies: Several Recmentioning
confidence: 99%
“…Pickpocket (ppk), the first subunit to be identified, is involved in locomotive behaviour in fruit fly larvae. Other ppk genes have been implicated in fluid re-distribution (Adams et al, 1998;Liu et al, 2003a), gustatory salt perception (Liu et al, 2003b), and male response to female pheromones . Preliminary analysis of the pea aphid genome has indicated that there are between 23 and 26 ppk genes present with conserved structural features, but low overall sequence similarity.…”
Section: Sodium Channel 60ementioning
confidence: 99%